THEORETICAL FUNDAMENTALS OF PROFESSIONAL FORMATION OF PEDAGOGICAL CULTURE OF THE FUTURE TEACHER IN THE PERIOD OF PEDAGOGICAL PRACTICE (Pedagogy of Higher and Secondary Education, 2004)
The problem of formation of the professional-pedagogical culture in the rip of the passing the pedagogical practice by students is examined in the article. Theoretic principles of treatment this problem are analyzed\ it is organized structure and levels its successful.